MeV ion irradiation effects on the luminescence properties of Si‐implanted SiO2‐thin films. Issue 10 (6th October 2016) - Chulapakorn, T.; Sychugov, I.; Suvanam, S. S.; Linnros, J.; Primetzhofer, D.; Hallén, A.
Abstract: The effects of MeV heavy ion irradiation at varying fluence and flux on excess Si, introduced in SiO2 by keV ion implantation, are investigated by photoluminescence (PL). From the PL peak wavelength (λ) and decay lifetime (τ), two PL sources are distinguished: i) quasi‐direct recombination of excitons of Si‐nanoparticles (SiNPs), appearing after thermal annealing (λ > 720 nm, τ ∼ μs), and ii) fast‐decay PL, possibly due to oxide‐related defects (λ ∼ 575‐690 nm, τ ∼ ns). The fast‐decay PL (ii) observed before and after ion irradiation is induced by ion implantation. It is found that this fast‐decay luminescence decreases for higher irradiation fluence of MeV heavy ions. After thermal annealing (forming SiNPs), the SiNP PL is reduced for samples irradiated by MeV heavy ions but found to stabilize at higher level for higher irradiation flux; the (ii) band vanishes as a result of annealing. The results are discussed in terms of the influence of electronic and nuclear stopping powers. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)